Screening of Cellulolytic Bacteria from Sugarcane Waste (Bagasse) and Optimization of Cellulase Activity as Animal Feed: Screening of Cellulolytic Bacteria from Sugarcane Waste (Bagasse) - Ramadhani, Sulistya Ika; Ardyati, Tri; Sjofjan, Osfar (Journal of Tropical Life Science, 2023)
The Sugar Factory of Tjoekir Jombang is one of the sugar factories located in Jombang, East Java under PT Perkebunan Nusantara X. Sugarcane waste, also known as bagasse causes pollution of the environment. Some microorganisms are able to degrade cellulose-containing bagasse, because of cellulolytic enzymes produced by cellulolytic bacteria. This study aims to obtain cellulolytic bacteria isolates, screen the highest cellulolytic activity, identify the highest cellulolytic activity isolates, and optimize conditions (pH and temperature) for the highest cellulase activity. Cellulolytic bacteria from bagasse were grown on a medium containing 1% CMC. Several additional minerals were other than those in the CMC medium. The cellulase activity was assayed semi-quantitatively with the addition of 0.1% Congo red and quantitatively using the 3,5-Dinitro Salicylic Acid (DNS) method. Bacterial isolates with high cellulolytic activity were identified based on the 16S rDNA sequence. This research obtained 20 bacterial isolates, where isolate A1T4 had the highest cellulolytic index of 1.18 mm. Measurement of cellulase activity using the DNS method showed that isolate A2T2 had the highest cellulase activity of 2.19 U/mL. Hemolysis assay showed that from 12 isolates, only two isolates have γ-hemolysis activity (isolates A1T6 and A3T3). Those isolates were optimized in a CMC broth medium with temperatures of 30°C and 37°C and pH 5 and pH 6 to produce the highest cellulase activity. Isolate A1T6 and A3T3 were grown optimally at 30oC and pH 6. Isolate A1T6 was identified as Citrobacter amalonaticus with a similarity of 99.80%, and isolate A3T3 was identified as Pseudomonas mendocina with a similarity of 98.83%.